Willingness-to-pay for environmental conservation and management of Nogas Island and its sorrounding waters among the residents of Anini-y, Antique. - Pedrina, Nichole Patricia B.
Nogas Island, located in the municipality of Anini-y, Antique Province, is endowed with natural resources that attract tourists in recent years. With its natural beauty and emerging popularity, the island and its surrounding waters have become more vulnerable to degradation brought about by human activities. Protection and conservation is necessary in order to ensure environmental sustainability. This study was conducted to determine the willingness-to-pay (WTP) of the local residents of Anini-y for the conservation of Nogas Island and its surrounding waters using Contingent Valuation Method (CVM). The study also described the socio-demographic and economic characteristics of the study participants, and their level of awareness, knowledge and attitude, and the reasons for their willingness to pay for the conservation of Nogas Island and its surrounding waters. A pilot-tested interview schedule was used to collect data from 320 randomly selected study participants in eight barangays in the municipality of Anini-y from January to March 2017. Binary logit regression was conducted to identify factors affecting the study participants? WTP. The results revealed that 62 percent and 55 percent of the study participants were willing to pay for the conservation program with and without adjustment for the level of certainty, respectively. The variables that significantly affect WTP, without adjustment for the level of certainty, were sex (10% level of significance), knowledge index (5% level of significance), and randomly assigned bid (at 1% level of significance); with adjustment for the level of certainty, these were knowledge index rating (10% level of significance) and monthly household income (at 5% level of significance). The monthly mean WTP of the study participants with and without adjustment for the level of certainty were P115 and P104.5, respectively. This study recommends that the local government of Anini-y pursue a strengthened program for the rehabilitation, protection, and conservation program fro Nogas Island.